Design and Test of a Secondary Shearing Device for the Lentinus Edodes Stem - Wang , Zhen; Xiao , Weizhong; Liu , Yuandong; Zhang , Yuting; Liu , Qin; Cui, Xiao; Kong, Weili (Journal of Engineering and Technological Sciences, 2025)
To address the high labor intensity and low efficiency in the manual stem cutting of Lentinus edodes (shiitake mushrooms), A secondary shearing device was designed. This device automated the shearing and separation of mushroom roots and stems, significantly improving the efficiency of the stem-cutting process. Evaluated through indicators such as productivity, pass rate, and damage rate, a four-factor and three-level response surface test was conducted. The test factors included tool velocity, stem length, number of blades, and conveying velocity. Using Design-Expert 12.0 software to analyze the test data, the optimal parameter combination was determined: a tool velocity of 5800 r/min, stem length of 28 mm, four blades, and a conveying velocity of 52.78 m/min. Under these conditions, the device achieved a productivity of 0.49 Kg/h, a pass rate of 91.18%, and a damage rate of 5.73%. Verification tests confirmed the reliability of these parameters, showing slight deviations from the experimental predictions but still meeting the requirements for Lentinus edodes stem cutting. This study demonstrated that the secondary shearing device could significantly reduce labor intensity and improve efficiency in mushroom cultivation practices. Future research should focus on integrating robotic systems for automation and exploring additional parameters to further enhance the device's performance.